Finders and keepers : - Johnson, Susan Moore (John Wiley & Sons, 2004)
America’s schools are changing rapidly, especially in urban areas, as one generation of teachers retires and more than two million new teachers enter the profession. In order for schools to both find and keep new teachers, Harvard education professor Johnson says, major reforms are needed in the ways they recruit, train and retain their staff. Over the course of three years, Johnson, who worked with Harvard’s Project of the Next Generation of Teachers, interviewed 50 teachers in Massachusetts as they began their teaching careers. Their experiences and recollections form the heart of this important book. New teachers, Johnson reveals, are no longer always products of college teacher-training programs; now, they might be mid-career transfers to the profession or young adults who have taken a few teaching courses before entering the classroom. Whatever the source of entry, the pressure on new teachers is enormous; Johnson writes that "one of the ‘givens’ of being a teacher is knowing you will not be able to do all that society asks of you." Many of the interviewees make it clear that they ended up working in isolation, without guidance from principals, veteran teachers or a set curriculum. Johnson insists that schools must "provide new teachers some shelter—a less demanding assignment or a slightly reduced load." She also recommends that schools overhaul their hiring practices, commence interviewing candidates in the spring instead of just before September, create systems for professional orientation, support collegiality, and keep teachers motivated by offering professional growth opportunities. No argument is more convincing than the statistics with which Johnson concludes: of the 50 teachers included in the study, 33% have already left teaching. This is a must-read for anyone involved in education.